2006
DOI: 10.2337/db06-0330
|View full text |Cite
|
Sign up to set email alerts
|

Altered Adipose and Plasma Sphingolipid Metabolism in Obesity

Abstract: The adipose tissue has become a central focus in the pathogenesis of obesity-mediated cardiovascular and metabolic disease. Here we demonstrate that adipose sphingolipid metabolism is altered in genetically obese (ob/ob) mice. Expression of enzymes involved in ceramide generation (neutral sphingomyelinase [NSMase], acid sphingomyelinase [ASMase], and serine-palmitoyl-transferase [SPT]) and ceramide hydrolysis (ceramidase) are elevated in obese adipose tissues. Our data also suggest that hyperinsulinemia and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
134
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(149 citation statements)
references
References 46 publications
11
134
2
2
Order By: Relevance
“…Our findings are substantially in keeping with a number of previous studies in animal models and humans showing that plasma levels of ceramides are increased in obesity (Samad et al ., 2006; Haus et al ., 2009; Huang et al ., 2011). In fact, obese persons frequently have lower aerobic capacity and mitochondrial dysfunction and the cause of such dysfunction is less than clear.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are substantially in keeping with a number of previous studies in animal models and humans showing that plasma levels of ceramides are increased in obesity (Samad et al ., 2006; Haus et al ., 2009; Huang et al ., 2011). In fact, obese persons frequently have lower aerobic capacity and mitochondrial dysfunction and the cause of such dysfunction is less than clear.…”
Section: Discussionmentioning
confidence: 99%
“…Although still under debate, recent studies have also demonstrated associations with thiazide‐based treatments and increased risk of type II diabetes and subsequently increased the risk of cardiovascular events 38, 39. Phosphoethanolamines are used in the construction of sphingolipids, and perturbations in sphingolipid metabolism have been implicated in adverse cardiovascular effects, have demonstrated the ability to alter insulin resistance, and in turn may be connected to increased risk of type II diabetes 40, 41, 42. We detected a statistically significant decrease in circulating O‐phosphoethanolamine in the black group exposed to HCTZ ( q  < .05), which may be due to an increase in sphingolipid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In obese rodents and humans ceramide is elevated in the liver, the hypothalamus and skeletal muscle (Adams et al, 2004;Holland et al, 2007). In leptindeficient ob/ob mice, total sphingomyelin and ceramide levels in adipose tissue are reduced, whereas circulating levels of sphingomyelin, ceramide, sphingosine and S1P are increased in plasma, since ceramide secretion by adipose tissue is increased (Samad et al, 2006). In addition, the inflammatory status associated with obesity overlaps with ceramide production.…”
Section: Sphingolipidsmentioning
confidence: 95%
“…In addition, the inflammatory status associated with obesity overlaps with ceramide production. TNF-a administration to mice results in an up-regulation of ceramide synthetic enzymes in adipose tissue, thus increasing ceramide production (Samad et al, 2006). Adiponectin, the levels of which are generally reduced in obesity and diabetes , is linked to sphingolipid metabolism.…”
Section: Sphingolipidsmentioning
confidence: 99%
See 1 more Smart Citation